Business models for Mobility as an Service - Vincent A.C. van den Berg; Henk Meurs; Erik T. Verhoef (Tinbergen Institute, 2022)
Travellers often combine transport services from different firms to form trip chains: e.g. first taking a train and then a bus. Integration of different forms of public and private transport into a single service is gaining attention with the concept of Mobility as a Service (MaaS). Usually the attention focuses on such things as ease of use for travellers and shifting demand away from the car. We focus on the effects of MaaS on behaviour and welfare via the market structure of transportation. In particular, we analyse three archetypical ways in which MaaS could be operationalised: Integrator, Platform, and Intermediary.
Keywords: R4; D21; D43; 330; MaaS; market structure; platform; intermediary; integrator; regulation